Implementasi Manajemen Kurikulum Merdeka untuk Meningkatkan Mutu Pendidikan - Firmansyah; N Hanafiah; Handayani, Sri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to describe and analyze the Implementation of Merdeka Curriculum Management to Improve Education Quality. The research approach uses a qualitative approach descriptive method. Data collection techniques using interviews, observation, and documentation. Research results: Planning stage with 1) Identification of Local Needs, 2) Organizing a Curriculum Planning Team. 3) Socialization of Understanding the Independent Curriculum Concept. 4) Determination of CP and ATP Learning Objectives. 5) Selection of teaching materials and project modules: 5) Planning Extracurricular Activities and Practical Learning. 6) Teacher Training. 7) Student and Community Engagement. 8) Evaluation and Renewal. The organizing stage begins with the formation of a curriculum committee consisting of experienced teachers from various fields of study. This committee is tasked with planning and overseeing curriculum implementation by the principles of the Merdeka Curriculum. The implementation of the Merdeka Belajar curriculum at SMPN 154 Jakarta involves the application of intracurricular and co-curricular learning. Within this framework, project-based learning is organized according to the themes set by the government. The evaluation process of the Merdeka Belajar curriculum at SMPN 154 Jakarta is carried out by compiling learning assessments which serve as an evaluation tool to assess the success and effectiveness of the curriculum implementation.